Microemulsion: A versatile synthesis tool for photocatalysis. (October 2020) - Kubacka, Anna; Caudillo-Flores, Uriel; Barba-Nieto, Irene; Muñoz-Batista, Mario J.; Fernández-García, Marcos
Abstract: Photocatalytic materials have complex nature, frequently with participation of multiple or complex multiatom components. These materials need to be synthesized with stringent control of their structural, morphological, and electronic properties in the quest to optimize functional properties. This is a challenge tackled with the help of the microemulsion method, which appears as a versatile tool to easily generate single or multicomponent catalysts. The review provides a perspective on this issue, highlighting the link between the control of physicochemical properties offered by microemulsion and the optimization of the photocatalytic activity. Graphical abstract: Image 1